The Night of the Unicorn - Nimmo, Jenny (Walker Books Ltd, 2003)
A meteor shower brings together two young children. One morning, after seeing shooting stars, Amber awakes to all sorts of discoveries. Hennie, her favourite hen, has vanished; a strange white horse has appeared at the animal sanctuary; and Luke Foster, the unhappy new boy at school, confides in Amber his impossible wish. But perhaps what Luke is looking for is not so impossible after all.
Keywords: Juvenile literature-English language-Fiction